Persepsi klien terhadap pendedahan kendiri kaunselor dalam sesi kaunseling : satu kajian kes - Muqri, Bin Mohd. Sofian (Universiti Malaysia Sarawak (UNIMAS), 2005)
The purpose of this research is to identify the client's perception towards counselors' self-disclosure in counseling sessions based on the seven elements which are interpersonal relations, personal feeling, sexual issues, professional issues, success and failure, attitudes, and experiences and expertise in problem solving. This research is also identifying the differences between the gender and the number of sessions with those elements. This research involves 86 respondents of form 5 and form 6 students from Yan area. Instrument use in this research is Client's Perception Questionnaire by Sabasiah Husin, 1998. The descriptive statistic method was used to analyze the demography of the respondent (frequency and percentages). Mean Score test is used to identify the clients' perception by range based on the lickert scale in the questionnaire. The t-test and Pearson Colleration is used to test the hypotheses formed. The findings shows that the clients are prefer their counselors to disclose all the elements except the sexual issues. The results of the study reveal that there is a significant difference between gender and the elements. There is also a significant colleration between number of sessions and those elements. The researcher suggests that the school counselors should aware while using the self-disclose technique based on the elements. The researcher also suggests to use larger scope and different sample to make this research more interesting in the future.